Analysis the Performance, Emission and Combustion of DI Diesel Engine Powered By Algae Methyl Ester - M. Arangarajan, A. Raja, W. Christ Raj (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper reports on the algae methyl ester is blended with diesel fuel in different percentage and the effects of their performance, combustion and emission characteristics of the DI diesel engine. In this study, the tested fuels were obtained through transesterification process. The properties of algae methyl ester (AME) analysed by ASTM standard methods. Experimental results showed that the cetane number and flash points of the algae methyl ester blended diesel have increased with higher concentration of AME. Based on the experimental results, HC and smoke emissions noticeably increase, while NOx emissions significantly decrease with increasing the dosing level of AME. From the results, B25 having nearer values in terms of combustion and emission to diesel fuel. At the full load, the magnitude of HC, smoke and NOx emissions for the neat diesel was 114 ppm, 72 HSU and 1120 ppm, whereas it was 116 ppm, 79 HSU and 1070 ppm for the B25 blend of AME fuel, respectively.